A Bible commentary for today - Howley, G.D.C.; Bruce, Frederick Fyvie, 1910-1990; Ellison, Henry Leopold, 1903- (London, UK Pickering and Inglis, 1979)
Includes bibliographical references.
Keywords: Bible -- commentaries